Safety enhancement of improved hydrodissection for microwave ablation in lymph node metastasis from papillary thyroid carcinoma: a comparative study - Jie Wu; Ying Wei; Zhen-long Zhao; Shi-liang Cao; Yan Li; Li-li Peng; Shu-qi Li; Ming-an Yu (Frontiers in Endocrinology, 2025)
PurposeThis study aims to evaluate the efficacy and safety of an improved hydrodissection technique based on the perilymph-nodal space (PLNS) when applied during microwave ablation for treating lymph node metastases (LNM) arising from papillary thyroid carcinoma (PTC).MethodsA retrospective analysis was conducted on data from 266 patients (95 males, 171 females, mean age 41.3 ± 14.0 years, range 16–88) who underwent MWA for LNM. Of these, 142 patients received traditional hydrodissection (traditional group), while 124 underwent the improved technique. Safety outcomes were assessed by comparing complication rates between the two groups. Additionally, the characteristics of the hydrodissected fascial spaces, complications, and follow-up results were documented.ResultsAll patients underwent successful hydrodissection as planned. The improved hydrodissection group demonstrated a lower incidence of hoarseness compared to the traditional group (4.8% vs. 8.4%, p >0.05). Notably, in region VI cases, the improved technique significantly reduced the incidence of hoarseness (7.5% vs. 25%, p = 0.006). Additionally, the median recovery time for hoarseness was shorter in the improved group (3 vs. 6 months, p <0.05). During follow-up, neither group exhibited local recurrence. The tumor disappearance rates were comparable between the groups (75.4% vs. 65.3%, p >0.05).ConclusionThe PLNS-based improved hydrodissection technique demonstrated enhanced safety compared to traditional hydrodissection during MWA for LNM, especially for region VI lesions.